Analysis of Factors Influencing the Performance of Female Civil Servants in Makassar City - Aswar, Nurul Fadilah (Economics and Business Journal (ECBIS), 2023)
This study examined the influence of Education and Training, Work Motivation, and Leadership Style on the performance of female Civil Servants (ASN) in the city of Makassar. Using a quantitative causal method, this research collected data from 100 samples determined based on the Slovin formula. Data analysis was conducted using multiple linear regression with SPSS version 25. The results of the study showed that all independent variables had a significant impact on employee performance. Validity and reliability tests confirmed the reliability of the research instrument. The regression model indicated that an increase in the variables of Education and Training, Work Motivation, and Leadership Style was positively associated with an improvement in employee performance. The coefficient of determination (Adjusted R Square) of 31% indicated that independent variables influenced 31% of the variance in employee performance, while the rest was influenced by other factors.This research confirms that education and training are important for improving the quality and performance of employees. Work motivation significantly affects performance, and effective leadership style positively contributes to employee performance. In conclusion, Education and Training, Work Motivation, and Leadership Style collectively and partially have a significant impact on the performance of female ASN employees in the city of Makassar.